Effect of Maleic Hydrazide and Waxing on Quality and Shelf-Life of Papaya (Carica papaya L.) Fruits (University of Khartoum Journal of Agricultural Sciences, 2023)
The effect of post-harvest treatment of Maleic hydrazide (MH)with and without waxing on the quality and shelf-life of ‘Baladi’ and‘Ekostika I’ papaya fruits at 18 ± 1 oC and 85% – 90% relative humiditywas evaluated. Maleic hydrazide at 250 and 500 ppm significantlydelayed fruit ripening by two and three days in both papaya cultivars,respectively, compared with untreated fruits. The higher theconcentration, the more was the delay in fruit ripening. The results alsoshowed that waxing in addition to MH resulted in a delay of two moredays in fruit ripening than treatment with MH alone. The effect of MHand waxing treatments in delaying papaya fruits ripening was manifestedin retarded respiratory climacteric, reduced weight loss and delayed fruitsoftening and increase in total soluble solids and ascorbic acid content
Keywords: Papaya fruits; maleic hydrazide; waxing; fruit quality; shelf- life